Energy Efficient Waveband Translucent Optical Burst Switching Network - Mohammed J. Sadiq; Mohammed J. Zaiter; Raad F. Chisab (Journal of Techniques)
The fast development of translucent Optical Burst Switching (OBS) technology, which employs multiple wavelengths per fiber, increases the size (i.e., the number of ports) as well as the cost and power consumption of Optic Cross-Connects (OXCs). This paper studies the impact of OBS network parameter settings, where switching is performed at the Waveband Switching (WS) granularity using an end-to-end grouping method to reduce the number of lightpaths and switch ports. The simulation results illustrate that using OBS networks with WS by the suitable parameter settings, namely the Burstification Time (BT) and waveband granularity, offers considerable energy savings in the core network compared to using an OBS network without WS, where overall power consumption is decreased by maximizing BT values and waveband granularity.